2013
DOI: 10.5433/1679-0359.2013v34n6supl2p3935
|View full text |Cite
|
Sign up to set email alerts
|

Efeito anti-helmíntico de taninos condensados em nematódeos gastrintestinais de ovinos (Ovis aries)

Abstract: ResumoAs helmintoses gastrintestinais constituem um dos principais fatores limitantes na produção de ovinos em todo o mundo. O desenvolvimento da resistência dos parasitos aos anti-helmínticos tem gerado grandes perdas na produção de pequenos ruminantes. Na busca por novas alternativas de controle efetivo de nematódeos gastrintestinais em pequenos ruminantes, a fitoterapia constitui um campo promissor de pesquisas na tentativa de reduzir a utilização de tratamentos químicos, visando uma produção agroecológica.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
1
3
0
12
Order By: Relevance
“…Among the phenolic compounds in guava, the tannin and flavonoid contents are (Chang et al 2013) considered promising substances in the control of helminths (Botura et al 2013, Yoshihara et al 2013. The content of condensed tannins found in PgHA were higher in the present study than Gonçalves et al (2016) in buckwheat (Fagopyrum esculentum), which also showed Table I.…”
Section: Resultssupporting
confidence: 59%
“…Among the phenolic compounds in guava, the tannin and flavonoid contents are (Chang et al 2013) considered promising substances in the control of helminths (Botura et al 2013, Yoshihara et al 2013. The content of condensed tannins found in PgHA were higher in the present study than Gonçalves et al (2016) in buckwheat (Fagopyrum esculentum), which also showed Table I.…”
Section: Resultssupporting
confidence: 59%
“…Considering that condensed tannins are identified as promising substances for the control of helminths ( ST T U et al, 2017;QUIJADA et al, 2015;QUIJADA et al, 2018;SHALDERS et al, 2014;SPIEGLER;LIEBAU;HENSEL, 2017;YOSHIHARA et al, 2013), the levels of condensed tannins present in 10 mg/mL HEB, may represent another important factor to justify the continuation of the present study.…”
Section: Resultsmentioning
confidence: 92%
“…Além dos efeitos nutricionais, os taninos condensados possuem um considerável efeito antihelmíntico, por favorecer a recuperação do epitélio e do sistema imune frente a verminose, assim como, por impedir o desenvolvimento das larvas no hospedeiro (Yoshihara et al, 2013). Apesar da grande eficiência e contribuição dos fármacos na melhora de produtividade de rebanhos, no momento atual, devido ao aumento contínuo do número de populações de helmintos resistentes aos antiparasitários disponíveis, enfatiza a necessidade de investimento em novas formas de controle (Scott et al, 2013).…”
Section: Introductionunclassified